The Effect of Work Flexibility, Work-Life Balance, and Job Satisfaction of Millennial Employees - Nur Ahdianita, Faras Cantika; Setyaningrum , Retno Purwani (Ridwan Institute, 2024)
Job satisfaction is a collection of feelings and beliefs that people have about their current job. Job satisfaction is also the employee's feelings towards the workers he does. Employee feelings towards work can be interpreted whether employees feel satisfied, comfortable, safe, and peaceful in doing or completing their work. The purpose of this study is to determine the effect of Flexible working arrangement and Work life balance on Job Satisfaction with Work engagement as a mediation variable. This study uses quantitative methods with the number of samples are employees of PT. Heintech Dwikarya Swapraja with a total of 171 respondents. This research was processed using SmartPLS data processing software and data collection was carried out through Google forms. Flexible Working Arrangement has a significant effect on Job Satisfaction, Flexible Working Arrangement has a significant effect on Work Engagement, Work-Life Balance has a significant effect on Job Satisfaction , Work Engagement as a mediation variable has a significant effect on Job Satisfaction, while some variables that do not affect Work Engagement do not have a significant effect on Job Satisfaction, Work-Life Balance does not have a significant effect on Work Engagement, Work Engagement as a mediating variable does not have a significant effect on Job Satisfaction